Basis epistemologi dalam Pendidikan Islam - Hanafi, Imam (Jurnal Pendidikan Islam, 2012)
In epistemology, Islam has a concept that is established more in translating science integration. When a Muslim does a scientific activity, then he should depart from the basic intentions and intrinsic motivation that comes out of the deepest conscience to meet the guidance of Allah. So that between science and con-science is unity and totality that lead to the soul of rabbaniyyat. While we are developing and exploring the concept of theoretical and practical, we must not just stop at the fact but also the fact behind the fact at the time of spiritual or metaphysical sense expressed in each statement of physics.